Pengembangan Model Pembelajaran Blended Learning pada Pendidikan Kesetaraan Program Paket C dalam Meningkatkan Kemandirian Belajar - Anan Sutisna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2016)
This research aimed at discovering a instructional model to improve self learning of students package C program. Alternative selected to reach the objective of this research to develop a instructional model of Blended Learning, focusing at self learning. The instructional model was developed based on the fact and consideration that the on going instruction process was regarded too conventional. Learning Blended learning model on the package C program is conducted by the method of research and development through three stages: a preliminary study, the preparation of conceptual models and test to determine the effectiveness of the model. The result showed that instructional model of Blended Learning is effective to improve the self learning of students package C program at the Center for Community Learning.